IgA Plasma Cells Are Long-Lived Residents of Gut and Bone Marrow That Express Isotype- and Tissue-Specific Gene Expression Patterns - Wilmore, Joel R.; Gaudette, Brian T.; Gómez Atria, Daniela; Rosenthal, Rebecca L.; Reiser, Sarah Kim; Meng, Wenzhao; Rosenfeld, Aaron M.; Luning Prak, Eline T.; Allman, David (Frontiers in Immunology, 2021)
Antibody secreting plasma cells are made in response to a variety of pathogenic and commensal microbes. While all plasma cells express a core gene transcription program that allows them to secrete large quantities of immunoglobulin, unique transcriptional profiles are linked to plasma cells expressing different antibody isotypes. IgA expressing plasma cells are generally thought of as short-lived in mucosal tissues and they have been understudied in systemic sites like the bone marrow. We find that IgA+ plasma cells in both the small intestine lamina propria and the bone marrow are long-lived and transcriptionally related compared to IgG and IgM expressing bone marrow plasma cells. IgA+ plasma cells show signs of shared clonality between the gut and bone marrow, but they do not recirculate at a significant rate and are found within bone marrow plasma cells niches. These data suggest that systemic and mucosal IgA+ plasma cells are from a common source, but they do not migrate between tissues. However, comparison of the plasma cells from the small intestine lamina propria to the bone marrow demonstrate a tissue specific gene transcription program. Understanding how these tissue specific gene networks are regulated in plasma cells could lead to increased understanding of the induction of mucosal versus systemic antibody responses and improve vaccine design.